DISKRIMINASI GENDER TERHADAP PEREMPUAN DALAM SEKTOR PEKERJAAN - Khusnul Khotimah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Gender ideology and patriarchal culture have resulted gender inequality, especially at occupation domain. Its can be seen from Workforce Participation level that dominated by men. There’s several factors influencing that inequality, include marginalization to women, on public or domestic domain. Woman subordination in social or cultural aspect also affects discrimination. Labeling (stereotyping) to women and lower education level also affect woman work participation. As a consequence, many women choose work activity at informal environment with very low wages and without health, law, and financial security